小波变换域自适应滤波器在传动误差测试中的应用 - 唐进元; 李松 (Jixie chuandong)
A kind of wavelet transform domain adaptive filter for signal denosing theory and its application in transmission error measuring are introduced,a new variable step size calculation formula is established.The gear transmission testing system is established based on the software LabVIEW of NI and related hardware,and the experiment verification is carried out.The result shows that,this filter can denoise the signal effectively and retain useful information,the practical value is high.